Branch-site occlusion sign predicts the embolic origin of acute ischemic stroke: a meta-analysis - Jiang, Xinzhao; Shi, Zongjie; Wang, Peng; Wang, Xu; Liu, Fang (Frontiers in Neurology, 2023)
Objective: To investigate whether branch-site occlusion (BSO) sign could predict the etiology of acute intracranial large artery occlusion (ILVO) and the stentriever (SR) response. Methods: We systematically reviewed studies that evaluated the predictive role of BSO for the etiology of ILVO-AIS or EVT outcome between January 1, 2000, and August 31, 2022fromPubMed, Embase, and Web of Science. Results: The sensitivity and specificity of BSO sign predicting etiology of ILVO-AIS were 0.87 (95% CI 0.81-0.91) and 0.64 (95% CI 0.33–0.87), respectively(fig.3A). The sensitivity and specificity of BSO sign predicting stentriever response were 0.84 (95% CI 0.63-0.94) and 0.61 (95% CI 0.18-0.92), respectively. Conclusion: BSO sign could be a valid and precise imaging marker to predict embolism caused ILVO-AIS and recanalization success by SR without rescue therapy.